Sustainable Catalytic Process for Fructose Dehydration using Dicationic Ionic Liquid Assisted ZSM-5 Zeolite. Issue 13 (3rd October 2021) - Prasad, Divya; Patil, Komal N.; Manoorkar, Vilas K.; Dateer, Ramesh B.; Nagaraja, Bhari Mallana; Jadhav, Arvind H.
ABSTRACT: In this work, a uniquely designed imidazolium-based dicationic ionic liquid (IL) was synthesized as a greener template and applied for the synthesis of ZSM-5 zeolite as a heterogeneous catalyst for the dehydration of fructose to 5-hydroxymethylfurfural (HMF). Characterization results confirmed that due to the presence of dicationic IL as template, effective interactions and structural alterations occurred during the construction of zeolitic framework wherein the vertices of ZSM-5 consisting of Al or Si and O elements were assumed to be bonded between the vertices of dicationic IL-assisted zeolite ZSM-5 catalyst. This resulted in superior structural advantages such as highly crystalline nature and stability as well as variation in mesopores when compared to commercial ZSM-5. Additionally, various reaction variables were investigated wherein synthesized dicationic IL-assisted ZSM-5 zeolite catalyst in the presence of [BMIm][Cl] as solvent demonstrated 95% conversion of fructose and 67.2% yield of HMF at 110°C within 90 min. The altered surface area and porous nature of synthesized ZSM-5 due to the presence of dicationic IL as template was responsible for the enhanced catalytic performance under mild reaction conditions. Most significantly, being a solid catalyst, the newly developed dicationic IL-assisted zeolite ZSM-5 catalyst showed recyclability for four recycles.